Sistem Pakar Untuk Mendiagnosa Kerusakan Pada Smartphone Berbasis Website Menggunakan Metode Forward Chaining - Budi Wahyu; Entis Sutrisna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In the age of globalization, the smartphone has become a very popular and important communication device for information. Yet, many smartphone users lack understanding of the upkeep, causing damage to the device, be it a software or hardware malfunction. This disrupts users and causes them to carry smartphones to mobile services, which takes considerable time and expense. Thus, in this study, the manufacture and development of a web-based software using forward chaining methods in experts' systems to detect smartphone damage. Forward chaining methods are suited for handling control and browsing problems. The website is designed to assist smartphone users in detecting damage, so they can repair their devices more quickly and efficiently. The case study used in this study is the plaza 08cell. Hopefully, with these webiste, smartphone users can easily and quickly solve their device's malfunction.